Crop Wild Relatives global atlas - Crop Wild Relatives and Climate Change (2013)
This atlas provides information on distributions and collecting priorities for the wild relatives of important crops. The application presents occurrence data points, potential distribution maps, and maps displaying areas identified as of priority for collecting for conservation and use. The maps can be explored per CWR taxon, as a summary per crop gene pool, or as a summary of all CWR in all assessed crop gene pools. See the "Related video" link for a tutorial on how to use this tool.